CONTROVERSIAL ASPECTS REGARDING APPOINTING AND REVOKING THE LEGAL ENTITY ADMINISTRATOR - CARMEN TODICA (Challenges of the Knowledge Society)
Having as main objective the analysis the provisions of Company Law and the New Civil Code regarding the management of a trading company by a legal person, the study offers several solutions to a number of controversial issues with strict reference to two aspects: appointing and revoking the legal entity administrator. Can the administrator be any entity with a legal personality or just a trade company? Is the administrator subject to legal requirements of good repute, characteristic to a representative natural person? Can the legal person fulfill the president position in a collective administrative body? Can he be revoked ad nutum? Regarding the administrator legal person representative, may the company revoke the administrator, on its own? There are several questions outlining the juridical status of the administrator legal person, and to which the paper tries to find answers, introducing some jurisprudence solutions, comparative law issues and controversial doctrinal views.